2018
DOI: 10.18203/issn.2454-5929.ijohns20185070
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative temporal bone HRCT and intra-operative findings in middle ear cholesteatoma: a comparative study

Abstract: Background: Middle ear cholesteatoma is a potentially dangerous condition owing to the varied extra-cranial as well as intra-cranial complications, it can be associated with. Clinical suspicion and otologic examination sufficiently identifies the pathology but its entire extent and spread is delineated by HRCT examination only, which is presently the "Gold Standard". In this study we tried to evaluate the efficacy of HRCT temporal bone in depiction of extent of pathology in cases of cholesteatoma of middle ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Our study showed male dominance which was similar to studies of Dashottar et al [4] and Kanotra et al [5]. To the best of our knowledge no previous literatures showed variety of ear diseases in such type of study in a single setting.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed male dominance which was similar to studies of Dashottar et al [4] and Kanotra et al [5]. To the best of our knowledge no previous literatures showed variety of ear diseases in such type of study in a single setting.…”
Section: Discussionsupporting
confidence: 92%
“…Our study noted lateral semicircular canal fistula in three (4.7%) diseased temporal bones. This observation was seen to concur with an HRCT study done by Dashottar et al in 50 symptomatic patients, which reported lateral semicircular canal fistula in two (4%) patients [15].…”
Section: Discussionsupporting
confidence: 91%
“…9 Mesotympanum involvement by disease was seen in all the patients compared to other study done by Dashottar et al where there was 96% involvement and 89% in study done by Ganotra. 2,4 Ossicular erosion was observed in 90% of patients in the study while it was found to be 89% in study done by Chavda et al 11 Similarly, lateral semi-circular canal involvement was observed in 6% patients while other study had 23% involvement. HRCT proved highly effective in showing ossicular erosion which correlated well intra-operatively, specifically for malleus and incus, similar to a study conducted by Rogha et al which showed good radio surgical correlation for malleus.…”
Section: Resultsmentioning
confidence: 65%
“…A high sensitivity and specificity (82-100%) of HRCT was found in detection of erosion of scutum, tegmen tympani and ossicles by Dashottar and higher sensitivity rates were found in my study for the same ranging from 90-100%. For facial canal erosion on HRCT, a sensitivity of 66% was found when compared to intra-op findings as compared to 50% in study done by Dashottar et al 2 HRCT temporal bone before surgery helped in carrying out pre-operative planning and evaluation and helped the surgeons in being more vigilant during the surgery. Also, it helped in planning for ossicular reconstruction.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation